River of life: the story of the Narmada bachao andolan - Gupta, Subhadra Sen; Guha, Tapas (ill.) (New Delhi The Energy and Resource Institute, 2016)
For Kanti the day began with startling news of the building of the Sardar Sarovar Dam over the River Narmada. Kanti was worried. Will they lose their home and livelihood as the waters of the dam bury their village? Where will they go? Was he seeing the sunrise by the banks of his much-loved river for the last time? There were too many questions with no easy answers. This gloomy situation for Kanti was a ray of hope for Deepal. She was excited, the construction of the dam would rid her life of water woes. Strange are the ways of the world with everything having a fl ipside. The River of Life is an insight into the lives of the tribal people of Madhya Pradesh and Gujarat. It chronicles people?s efforts to save their way of life and their rights to land and river as they were soon going to be displaced by the giant Sardar Sarovar Dam. About Series: Caring for Nature series focuses on some important unforgettable stories of people?s movements, such as Chipko Andolan and Silent Valley Movement, among others to save their forests, rivers, or land from greedy interests.
Keywords: Children story book